Fire resistance simulation of loaded deck sandwich panel and deck-bulkhead assembly structures - Mosallam, Ayman; Abdi, Frank; Qian, Zhongyang (Composites. Part B, Engineering, 2008)
In this study, fire resistance of a deck sandwich panel and deck-bulkhead assembly structures subject to service mechanical loads and to the action of fire is considered. The deck panel mid-span deflection was chosen as a criterion for the fire resistance assessment of both structures. Two simulation approaches were employed to determine the deck panel mid-span deflections. In the first approach, the GENOA progressive failure analysis software was used to evaluate the damage in the structure based on the equivalent temperature load profile predicted by thermal analysis. In the second approach, coupled thermal–progressive failure simulation was performed on the structure where the progressive failure analysis was invoked immediately after the temperature redistribution had been calculated for each time interval. In both approaches, the effect of fire on the bottom part of the deck panel was simulated through the application of surface heat fluxes to the bottom of the panel to calculate the equivalent temperature load required for the progressive failure analysis. The calculated mid-span deflection of the simply supported deck sandwich panel, after one-hour exposure to fire, correlated well with the experiment performed at Clemson University. Both the simulation and experimental results show that the mid-span deflection was significantly below the 2-ft deflection limit. In addition, the initiation and propagation of damage and fracture patterns over the deck structures were computed.